Murine Immune Response to a Chronic Staphylococcus aureus Biofilm Infection - Prabhakara, Ranjani (American Society for Microbiology (ASM), 2011)
Staphylococcus aureus has reemerged as an important human pathogen in recent decades. Although many infections caused by this microbial species persist through a biofilm mode of growth, little is known about how the host's adaptive immune system responds to these biofilm infections. In this study, S. aureus cells adhered to pins in culture and were subsequently inserted into the tibiae of C57BL/6 mice, with an infecting dose of 2 × 10(5) CFU. This model was utilized to determine local cytokine levels, antibody (Ab) function, and T cell populations at multiple time points throughout infection. Like human hosts, S. aureus implant infection was chronic and remained localized in 100% of C57BL/6 mice at a consistent level of approximately 10(7) CFU/gram bone tissue after day 7. This infection persisted locally for >49 days and was recalcitrant to clearance by the host immune response and antimicrobial therapy. Local inflammatory cytokines of the Th1 (interleukin-2 [IL-2], IL-12 p70, tumor necrosis factor alpha [TNF-α], and IL-1β) and Th17 (IL-6 and IL-17) responses were upregulated throughout the infection, except IL-12 p70, which dwindled late in the infection. In addition, Th1 Ab subtypes against a biofilm antigen (SA0486) were upregulated early in the infection, while Th2 Abs and anti-inflammatory regulatory T cells (Tregs) were not upregulated until later. These results indicate that early Th1 and Th17 inflammatory responses and downregulated Th2 and Treg responses occur during the development of a chronic biofilm implant infection. This unrestrained inflammatory response may cause tissue damage, thereby enabling S. aureus to attach and thrive in a biofilm mode of growth.